Partial Oxidation of Ethane to Acetic Acid on Titania Supported MoVNbPd Catalyst - S. Al-Zeghayer, Yousef; S. Al-Awadi, Abdulrhman; Y. Jibril, Baba; A. Soliman, Moustafa; Al-Mayman, Sulaiman (Asian Journal of Chemistry, 2013)
Partial oxidation of ethane was studied on unsupported and supported Mo-V-Nb oxides. Different grades of titania (Crystal-AF4.60, AF7.70 and AF12.5 and Degussa P25) were explored as supports. Samples of the catalyst were characterized using XRD, SEM and BET surface area. The reaction was carried out at 200-275 ºC and 200 psi. At ethane conversion (6 %), unsupported samples exhibited selectivities to ethylene and acetic acid of 76 and 23 %, while for Degussa P25-supported sample, the values were 54 and 35 %, respectively. Addition of Pd (0.196 %) led to an increase in selectivity to acetic acid of 75 %.